A novel method for deriving thresholds of toxicological concern for vaccine constituents. (3rd May 2016) - White, Jennifer; Wrzesinski, Claudia; Green, Martin; Johnson, Giffe T.; McCluskey, James D.; Abritis, Alison; Harbison, Raymond D.
Abstract: Safety assessment evaluating the presence of impurities, residual materials, and contaminants in vaccines is a focus of current research. Thresholds of toxicological concern (TTCs) are mathematically modeled levels used for assessing the safety of many food and medication constituents. In this study, six algorithms are selected from the open-access ToxTree software program to derive a method for calculating TTCs for vaccine constituents: In Vivo Rodent Micronucleus assay/LD50, Benigni–Bossa/LD50, Cramer Extended/LD50, In Vivo Rodent Micronucleus assay/TDLo, Benigni–Bossa/TDLo, and the Cramer Extended/TDLo. Using an initial dataset ( n  = 197) taken from INCHEM, RepDose, RTECS, and TOXNET, the chemicals were divided into two families: "positive" – based on the presence of structures associated with adverse outcomes, or "negative" – no such structures or having structures that appear to be protective of health. The final validation indicated that the Benigni–Bossa/LD50 method is the most appropriate for calculating TTCs for vaccine constituents. Final TTCs were designated as 18.06 μg/person and 20.61 μg/person for the Benigni–Bossa/LD50 positive and negative structural families, respectively.